Pengaruh Metode Demonstrasi Pada Pembelajaran Fiqih Thaharah Terhadap Kemampuan Bersuci Siswa Di MTs Swasta PAB 1 Helvetia - Putri, Sofie Khairina; Masitha, Widya (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
The demonstration method is a learning system that practices and shows directly about something that is learned by students. The purpose of this study was to determine the effect of learning fiqh thaharah on the ability to purify students at MTs PAB 1 Helvetia. The population in this study was class VII MTS PAB 1 Helvetia which consisted of four classes, namely class VII A, B, C, and D while the sampling technique used in this study was a non-probability sampling technique of purposive sampling so that a total of 92 samples were obtained. people taken from 4 classes with a total number of men as many as 45 people and women totaling 47 people, the data analysis technique used in this study was a different test, while the results of this study were The results showed that there was a change in grades in students who became the control class research after conducting demonstrations on thaharah fiqh learning on the ability to purify, there is a correlation between the average results of the ability to purify students for the pre-test for the experimental class and the post-test experiment (Demonstration method), the difference in the average results for the ability to purify students for the pre-test control class with post-test control and this research accepts the hypothesis that there is an effect of the demonstration method on learning fiqh thaharah on the ability to purify class VII students at MTs PAB 1 Helvtia.